If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n-5n+6=0
We simplify the equation to the form, which is simple to understand
n-5n+6=0
We move all terms containing n to the left and all other terms to the right.
+1n-5n=0-6
We simplify left and right side of the equation.
-4n=-6
We divide both sides of the equation by -4 to get n.
n=1.5
| x^2+3x+3=9 | | 0=-16x^2-2x+1 | | -6+8x=-36 | | (x+3)(x+3)(x+3)-3=x(x+8)(x+1)-1 | | 3x-12y=39 | | 14+5=14 | | -3=7n | | -3(1-9z)-1(-11z-11)= | | 6x-7=7x+15 | | 7.42=2(3.14)r | | 16x^2+2x-1=0 | | 32=r(16) | | 8-6y=4x | | .15x+.5(x-2)=(5x-4) | | n+2-34n=-8-33n | | -5(3-4c)-3(-c-4)= | | 470=2l+2(137) | | a(c+d)+2(c+d)=0 | | 4-3(x+3)=5x-5 | | 2(5)+8=0.25x | | 0.5(6x-14)=23 | | 7a^2b^4-27a^2b=0 | | 3v-9v=-52 | | m-38=-22 | | -3(9c-3)+5(c+1)= | | 11-6M=6(2-M) | | 0.45+0.05(18-x)=0.10(-39) | | 3-3A=3(-1+3A)6A | | 4y-(y-4)=-110 | | 11=0.3a+2 | | 3(x+2*5)=2x+5(5) | | 10(-3x+1)=-12(x+2)+34-18x |